Aerodynamics of shuttlecocks - Chia, Jiun Wei. (2013)
The popularity of Badminton sports has gained significantly over the years with the invention of synthetic shuttlecock which is lower in cost and more durable. However, a synthetic shuttlecock that exactly mirrors the flight of feather shuttlecock is yet to be produced. The purpose of this study is to understand the aerodynamics properties of feather shuttlecock by doing various experiments in outdoor and wind-tunnel.